Venezuelan equine Encephalomyelitis virus infection: Effect on Dopamine metabolism of mouse brain. Preliminary communication - Bonilla, Ernesto; Ryder, Slavia (Investigación Clínica, 2013)
Inoculation of VEE virus to mice produces an increase in brain dopamine and homovanillic acid. This rise possibly results from an increase in the levels of L-Tyrosine hydroxylase.